Investigation of Endoparasites in tow lessepsian fish species Saurida undosquamis and Stephanolepis diaspros in the Syrian Marine waters - حسن محمد; لايقة تغريد; حسون ياسر (Latakia University Journal -Biological Sciences Series, 2021)
This study aimed at investigating the Endoparasites in two lessepsian fish species, Saurida undosquamis and Stephanolepis Diaspros in the Syrian marine waters. A total of 250 individuals; 150 of Saurida undosquamis and 100 of Stephanolepis diaspros, were collected from marine waters of Lattakia. Stomach and intestine were removed and examined for parasitic infection. We isolated in this study for the first time in the Syrian marine waters, one endoparasite species Hysterothylacium aduncum that belongs to the Nematodes from the inferior part of intestine. The results showed that the prevalence was 30.6% and the intensity 1,9 in Saurida undosquamis, whereas these values were 34% and 2.4 respectively in Stephanolepis diaspros . Our results recorded highest infections by the isolated endoparasite species in spring in both studied fish species.